2002
DOI: 10.2527/2002.8051299x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of lean growth rate on puberty attainment in gilts2

Abstract: Two hundred sixteen prepubertal Genex Manor hybrid F1 gilts were used to determine the impact of lean growth rate on sexual development of gilts. This study was composed of two experiments (Exp. 1 and Exp. 2). In Exp. 1, at approximately 96 d of age and 54 kg weight, gilts were allocated with respect to growth rate and litter origin to one of two dietary treatments: 1) a diet formulated to maximize lean growth potential (LP; n = 84) or 2) a diet formulated to produce a lower lean growth rate (LL; n = 84). In E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
15
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 31 publications
4
15
0
1
Order By: Relevance
“…AA gilts had lower meat percentage and muscle thickness, higher fat thickness and lower ham width compared with GG gilts (Van den Broeke et al, 2015). Our results are therefore in accordance with the results of Rozeboom et al (1995) and Patterson et al (2002), that is that no association can be found between body conformation and the attainment of puberty in gilts.…”
supporting
confidence: 89%
“…AA gilts had lower meat percentage and muscle thickness, higher fat thickness and lower ham width compared with GG gilts (Van den Broeke et al, 2015). Our results are therefore in accordance with the results of Rozeboom et al (1995) and Patterson et al (2002), that is that no association can be found between body conformation and the attainment of puberty in gilts.…”
supporting
confidence: 89%
“…Although current industry practices avoid severely over-or underfeeding gilts during the developmental period, relatively little information is available regarding the effects of energy/nutrient intake on prepubertal estrus expression and subsequent sow productivity. Patterson et al (2002) compared the effects of diets formulated to maximize lean gain vs. reduced energy/lysine diets on puberty attainment in gilts. Age at puberty was not affected by average lean growth from 50 kg to 135 d of age (initiation of boar stimulation/ heat detection).…”
Section: Discussionmentioning
confidence: 99%
“…To develop practical gilt developmental regimens, it will be important to know effects on lifetime production. Several studies have examined the effects of nutrient manipulation during the growth period, gestation, or both on reproductive performance during the subsequent lactation (Hoppe et al, 1990;Newton and Mahan, 1993;Patterson et al, 2002). Our experiment is the first designed to examine the effects of genetic line and feeding regimen (energy intake) on gilt development and subsequent reproduction through 4 parities.…”
Section: Discussionmentioning
confidence: 99%
“…It has been postulated that a certain level of body condition is necessary for puberty attainment in gilts (Gaughan et al, 1997), whereas dietary treatments do not seem to affect pubertal age (Patterson et al, 2002). However, gilts with greater growth rate and backfat have shorter weaning to estrus intervals (Tummaruk et al, 2001) and age at puberty is positively genetically correlated with weaning to estrus interval and signs of estrus (Sterning et al, 1998).…”
Section: Discussionmentioning
confidence: 99%